Paired Tumor-Normal Sequencing Provides Insights Into the TP53-Related Cancer Spectrum in Patients With Li-Fraumeni Syndrome. (8th July 2021) - Ceyhan-Birsoy, Ozge; Selenica, Pier; Chui, M Herman; Jayakumaran, Gowtham; Ptashkin, Ryan; Misyura, Maksym; Aypar, Umut; Jairam, Sowmya; Yang, Ciyu; Li, Yirong; Mehta, Nikita; Kemel, Yelena; et al.
Abstract: Background: Genetic testing for Li-Fraumeni syndrome (LFS) is performed by using blood specimens from patients selected based on phenotype-dependent guidelines. This approach is problematic for understanding the LFS clinical spectrum because patients with nonclassical presentations are missed, clonal hematopoiesis–related somatic blood alterations cannot be distinguished from germline variants, and unrelated tumors cannot be differentiated from those driven by germline TP53 defects. Methods: To provide insights into the LFS-related cancer spectrum, we analyzed paired tumor-blood DNA sequencing results in 17 922 patients with cancer and distinguished clonal hematopoiesis–related, mosaic, and germline TP53 variants. Loss of heterozygosity and TP53 mutational status were assessed in tumors, followed by immunohistochemistry for p53 expression on a subset to identify those lacking biallelic TP53 inactivation. Results: Pathogenic/likely pathogenic TP53 variants were identified in 50 patients, 12 (24.0%) of which were clonal hematopoiesis related and 4 (8.0%) of which were mosaic. Twelve (35.3%) of 34 patients with germline TP53 variants did not meet LFS testing criteria. Loss of heterozygosity of germline TP53 variant was observed in 96.0% (95% confidence interval [CI] = 79.7% to 99.9%) of core LFS spectrum–type tumors vs 45.5% (95% CI = 16.8% to 76.6%) of other tumors and 91.3% (95% CI = 72.0% to 98.9%) of tumors from patients who met LFS testing criteria vs 61.5% (95% CI = 31.6% to 86.1%) of tumors from patients who did not. Tumors retaining the wild-type TP53 allele exhibited wild-type p53 expression. Conclusions: Our results indicate that some TP53 variants identified in blood-only sequencing are not germline and a substantial proportion of patients with LFS are missed based on current testing guidelines. Additionally, a subset of tumors from patients with LFS do not have biallelic TP53 inactivation and may represent cancers unrelated to their germline TP53 defect.